MANAJEMEN PEMBENTUKAN KERJASAMA GURU DAN ORANGTUA DALAM MENINGKATKAN MOTIVASI DAN KEMANDIRIAN BELAJAR PESERTA DIDIK - Nurhasanah; Ahmad Fauzan; Fisman Bedi (STKIP Subang, 2023)
Collaboration Between Teachers And Parents Is Important In Order To Build The Same Perception Between Schools And Parents In Supporting The Learning Process That Will Be Provided. This Research Aims To Determine The Form Of Collaboration Between Teachers And Parents In Increasing Students' Learning Motivation And Learning Independence. This Research Is Qualitative Research. The Results Of This Research Are Forms Of Collaboration Carried Out By Teachers And Parents In Increasing Learning Motivation, Including Having Good Communication Relationships, A Sense Of Mutual Trust Between Teachers And Parents In Monitoring Students, Teachers Not Covering Up Students' Shortcomings (Talking As They Are), Giving Homework. To Students, And Holding Regular Meetings At The End Of Each Semester As A Form Of Evaluating Student Deficiencies. And Independence Is Collaboration Between Parents And Teachers Through Virtual Online And Non-Virtual Online Means. Conclusions Can Be Drawn About The Form Of Collaboration Carried Out By Teachers And Parents In Increasing Learning Motivation And Learning Independence.